DEVELOPMENT AND VALIDATION OF A PROGNOSTIC MODEL OF MORTALITY IN PD. Issue 12 (15th November 2016) - Macleod, Angus; Dalen, Ingvild; Tysnes, Ole-Bjørn; Larsen, Jan Petter; Counsell, Carl
Abstract : Objectives: To develop a prognostic model to predict mortality in Parkinson's disease (PD). Background: Prognostic models can be used for individual prediction, case-mix correction, and clinical trial design. No prognostic model has been published for use in PD. Methods: The PINE study (198 patients) and ParkWest study (192 patients) are community-based, incidence cohorts of PD with lifelong prospective follow-up in North-East Scotland and Western Norway, respectively. In each study area, all incident cases were identified with community-based ascertainment strategies (2004–6 and 2006–9 in PINE; 2004–7 in ParkWest). Clinical predictors measured at diagnosis in the PINE cohort were combined to create a prognostic model of mortality using Weibull regression. It was externally validated by measuring calibration (observed versus predicted risk in quantiles of risk) and discrimination in the ParkWest cohort. Results: Independent baseline prognostic factors in the PINE study were age, male sex, higher co-morbidity, more bradykinesia, and more axial relative to limb features. The model combining these factors had good discrimination in the ParkWest cohort (C-statistic=0.77) but tended to underestimate survival. Conclusions: The model discriminated well and can therefore be used for case-mix correction or patient selection/stratification in trials. Recalibration may be necessary before making individualised predictions in other settings.